The Effectiveness of Digital-Based Population Administration Services in Supporting the Smart Village Program(Study in Bajak II Village, Merigi Kelindang District, Central Bengkulu Regency): Efektivitas Pelayanan Administrasi Kependudukan Berbasis Digital dalam Menunjang Program Desa Smart Village(Studi di Desa Bajak II Kecamatan Merigi Kelindang Kabupaten Bengkulu Tengah) - Edo Prayogo; Henny Aprianty; Bobby Mandala Putra (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This study analyzes the effectiveness of digital-based population administration services in supporting the Smart Village Program in Bajak II Village, Merigi Kelindang District, Central Bengkulu Regency. The research used a descriptive qualitative approach. Data were collected through interviews, observation, and documentation involving village officials and community members as service users. The data were analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The analysis refers to Sutrisno's effectiveness indicators: program understanding, target accuracy, timeliness, goal achievement, and tangible change. The findings show that digital-based population administration services in Bajak II Village have been implemented quite effectively. Digital services simplify access, shorten document-processing time, improve administrative order, and support the Smart Village agenda. Nevertheless, implementation still faces technical and nontechnical constraints, especially unstable internet connectivity, limited facilities, and varying digital literacy among residents.